2020
DOI: 10.1186/s12870-020-02706-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the compatible and incompatible interactions between sugar beet and the beet cyst nematode

Abstract: Background Sugar beet (Beta vulgaris subsp. vulgaris) is an economically important crop that provides nearly one third of the global sugar production. The beet cyst nematode (BCN), Heterodera schachtii, causes major yield losses in sugar beet and other crops worldwide. The most effective and economic approach to control this nematode is growing tolerant or resistant cultivars. To identify candidate genes involved in susceptibility and resistance, the transcriptome of sugar beet and BCN in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 82 publications
2
19
2
1
Order By: Relevance
“…Three biological replicates, each consisting of four pooled plants, were used per treatment. Library preparation, sequencing and data analysis were as in (Ghaemi et al, 2020). Briefly, libraries were prepared using the QuantSeq 3' mRNA-Seq library prep kit (Lexogen), library quality was verified using an Agilent Bioanalyzer 2100 and libraries were sequenced on an Illumina NextSeq 500 platform.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Three biological replicates, each consisting of four pooled plants, were used per treatment. Library preparation, sequencing and data analysis were as in (Ghaemi et al, 2020). Briefly, libraries were prepared using the QuantSeq 3' mRNA-Seq library prep kit (Lexogen), library quality was verified using an Agilent Bioanalyzer 2100 and libraries were sequenced on an Illumina NextSeq 500 platform.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…1,029 genes were upregulated, and 180 genes were down-regulated at at least onetime point in both A2-J and A2-O infected plants (Figure 2B). Previous studies showed that the expression of genes associated with the salicylic acid (SA), jasmonic acid (JA), and ethylene (ET) signaling pathways are induced in resistant plants infected with PPNs (Ye et al, 2017;Zhang H. et al, 2017;Bali et al, 2019;Du et al, 2020;Ghaemi et al, 2020), so we investigated the expression of marker genes for hormone biosynthesis, hormone signaling (Figure 2C), and defense responses (Figure 2D). Infection with A2-O significantly induced the expression of SA-regulated genes that encode basic pathogenesis-related protein 1 (PR1) and β-1,3glucanase (PR2), as well as a JA biosynthesis gene (lipoxygenase D (LoxD)), the JA-regulated gene protease inhibitor II (PI-II), and two ET biosynthesis genes (1-aminocyclopropane-1-carboxylate synthase (ACS) and 1-aminocyclopropane-1-carboxylate oxidase (ACO)) (Farmer et al, 1992;Yan et al, 2013;Booker and DeLong, 2015;Zhang et al, 2018;Marhavý et al, 2019;Figure 2C).…”
Section: Rna-seq Analysis Of S Torvum Root Tips Infected With A2-o or A2-jmentioning
confidence: 99%
“…Three biological replicates, each consisting of four pooled plants, were used per treatment and time point. Library preparation, sequencing and data analysis were performed as described in Ghaemi et al (2020). For each time point, Gene Ontology (GO) enrichment analysis was performed using G:PROFILER (Raudvere et al, 2019) on significantly differentially expressed genes (FDR-adjusted P < 0.05 and |log 2 -FC| > 0.7).…”
Section: Gene Expression Analysis Through Mrna Sequencingmentioning
confidence: 99%